Integrated Framework for Design & Testing of a Low-Solidity Vertical Axis Water Turbine for Renewable Micro-Hydro Applications - Irum, Saba; Abbas, Saram; Ibraheem, Muhammad (International Journal of Innovative Research in Computer Science and Technology, 2025)
With fast growing requirements of energy, discovery and using innovative and non- conventional energy sources are necessary. Hydro power is major source of substitute energy which would go unexploited otherwise if not extracted though some mechanical means. Pakistan is rich in shallow and high velocity stream water channels which carry significant energy potential. Lift based vertical axis water turbines such as Darrieus turbines are capable of generating large amount of energy with much simpler mechanism than conventional horizontal axis water turbines making it cost effective just by placing them in flowing water with substantial potential. However, low solidity vertical axis water turbines absence self-start capability due to low lift and higher required torque at beginning. Designed configuration was analysed by DMS theory in QBlade software and was then tested in actual water passage after fabrication.